Tafsir Historis Kritis Terhadap Matius 5:27-31 - Desy Mariana Siringoringo; Berlina Simatupang; Andika Sinaga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research examines Pastor GPP Siaro's views on defending the faith in the congregation, with a special focus on the interpretation of Romans 10:14. This verse highlights the importance of preaching the Gospel and the vital role of preachers in strengthening the congregation's faith. Through a qualitative approach, this research explores how Pastor GPP Siaro applies the principles of Romans 10:14 in his pastoral context. Research findings show that Pastor GPP Siaro emphasizes the importance of in-depth teaching, conveying God's word that is relevant to the context of the congregation, as well as empowering the congregation to be active in evangelistic missions. Pastor GPP Siaro also views that defending the faith is not only the task of church leaders, but is the responsibility of every member of the congregation. This research provides valuable insight into effective pastoral strategies in defending and strengthening faith in congregations, as well as the contribution of Bible verses in shaping theological and pastoral practice